Pengaruh Strategi Pengelolaan Keuangan Dan Manajemen Risiko Keuangan Terhadap Kondisi Keuangan Dalam Kehidupan Sehari-Hari Bagi Masyarakat Perum 2 Prambanan Kota Tangerang - Ridha Raya Dinayah; Aulia Kaila Rohmah; Alya Fitria Sari; Ela Nurlaela; Yanti Susanti (JURIBMAS : Jurnal Hasil Pengabdian Masyarakat, 2025)
Abstract This study aims to analyze the influence of financial management strategies and financial risk management on the financial condition of housewives in daily life. A quantitative approach with a descriptive method was used, implemented through a financial literacy-based educational training involving 40 housewives as respondents. Data were collected using pre-test and post-test questionnaires, then analyzed using multiple linear regression tests, t-tests, F-tests, and the coefficient of determination with the assistance of IBM SPSS Statistics 25. The results show that financial risk management strategies (X2) have a significant influence on the financial condition (Y), both before and after the training. In contrast, financial management strategies (X1) do not show a statistically significant effect, although there was an increase in the average score. However, when tested simultaneously, the combination of strategies X1 and X2 has a positive and significant influence on the respondents' financial condition. These findings emphasize the importance of synergy between financial planning and risk mitigation in strengthening household financial resilience.